Problemy dewastacji i ochrony powierzchni ziemi oraz walorów przyrodniczych w części zlewni Kłodnicy objętej wpływami górnictwa węgla kamiennego = Problems of devastation and protection of ground surface and of natural values in part of River Kłodnica basin embraced with influences of coal mining - Wrona, Andrzej; Harabin, Zdzisław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The deformations of ground surface caused by coal mining with collapse manner and storage of waste mining materials take the first place in destructive influence of mining. In report one presented the main problems of devastation and protections range of ground surface and of natural values in the river Kłodnica basin embraced with greatest harms caused by coal mining. One chose area carrying out 251 km2 for estimation, administratively embracing part of communes: Katowice, Chorzów, Ruda Śląska, Zabrze, Gliwice, Mikołów and Gierałtowice.
Keywords: 2 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zagospodarowanie zlewni" (21-22.06.2001)